Immunomodulatory properties of subcellular fractions of a G+ bacterium, Bacillus firmus - Cechova, Dana; Novakova, Michaela; Mikulik, Karel; Novotna, Olga; Julak, Jaroslav; Zanvit, Peter; Prokesova, Ludmila (Folia microbiologica, 2013)
Mucosal immunization with non-living antigens usually requires the use of an adjuvant. The adjuvant activity of Bacillus firmus in the mucosal immunization of mice was described by our laboratory previously. In the present study, subcellular localization of B. firmus activities was followed. After mechanical disintegration, subcellular components of bacterium were fractionated by differential centrifugation and salting out. Bacterial cell walls, cytoplasmic membrane fraction, soluble cytoplasmic proteins, and ribosomal fractions were isolated. Their effect on the mouse immune system was studied. Lymphocyte proliferation and immunoglobulin formation in vitro were stimulated by bacterial cell wall (BCW), cytoplasmic membrane (CMF), and ribosomal fractions. BCW and CMF increased antibody formation after intratracheal immunization of mice with influenza A and B viruses, and increased protection against subsequent infection with influenza virus. The BCW fraction even induced intersubtypic cross-protection: Mice immunized with A/California/7/04 (H3N2) + BCW were resistant to the infection by the highly pathogenic A/PR/8/34 (H1N1) virus.
Keywords: Orthomyxoviridae Infections; kultivované buňky; Influenza B virus; virus chřipky A; Bacillus; tvorba protilátek; Lymphocytes; vakcíny proti chřipce; Disease Models, Animal; lymfocyty; Mice; Cell Proliferation; Influenza Vaccines; Antibody Formation; virus chřipky B; Cells, Cultured; modely nemocí na zvířatech; zvířata; Influenza A virus; infekce viry z čeledi Orthomyxoviridae; myši; proliferace buněk; adjuvancia imunologická; Adjuvants, Immunologic; Animals